Geometrial: Development of Educational Digital Game for Combined Two-Dimensional Figure Learning - Ahmad Fairuzabadi; Herman Tolle; Fitra A Bachtiar; Ahmad Afif Supianto (Faculty of Computer Science (FILKOM) Brawijaya University, 2022)
Mathematics is one of the subjects that is often considered difficult and boring for students. This is evidenced by the poor scores obtained by the students. One of the chapters that are considered difficult is the geometry chapter, especially on the topic of combined two-dimensional figures studied by students at the Vocational High School (SMK) level. Spatial skills are needed for students to be able to solve combined two-dimensional figures questions, which to learn will be very difficult without using assisted learning media. While the learning so far is still using the conventional learning approach which is considered boring for students. This is due to the absence of learning media that is fun and can be easily accessed by students. This study tries to present a solution to this problem in the form of a mobile-based educational digital game design that can be accessed by all students. This digital educational game is called Geometry. This study uses Research & Development (R&D) combined with the Agile-Extreme Programming method to develop this educational digital game. Tests were carried out using an expert validation approach to game prototypes. This study uses a questionnaire that adapts the Computer System Usability Questionnaire (CSUQ) to assess the usability aspect of the game system built. Meanwhile, to assess this game from the point of view of educational media, this study used an evaluation questionnaire of material experts and media experts. The development process occurs in 3 iterations of development which includes the ideation, conceptualization, and prototyping stages. The results obtained from the assessment of material experts are 88.9% in the aspect of material suitability, and 85.7% in the suitability aspect of learning evaluation. While the results of the assessment obtained from media experts were 77.1% on the software engineering aspect, 76.3% on the visual design aspect, 80% on the media design aspect, and 77.6% on the system usability aspect (CSUQ).